Atención psicológica para pacientes con cáncer y sus familiares: ¿qué nos encontramos en la práctica clínica? - Fernández Sánchez, Belén; Jorge Martin, Vanesa; Sánchez Vázquez, Carmen María; Bejar Alonso, Eva (Psicooncología, 2017)
Facing a cancer diagnosis has a strong emotional impact on both patient and family because, in addition to the clear threat to health posed affecting all areas of life, which can lead them to demand psychological attention. Therefore, the objective of this study is to determine the usual clinical setting in oncology, analyzing for this, a sample of patients and relatives (n = 4,924) of the counseling service of AECC. The instruments used in the methodology are a self-report, specifically the distress thermometer (DT), and an interview. The results show that the profile of the primary beneficiary of psychological care in the AECC is female (72%), 55 ages, married or in a stable relationship (64%), which is also a patient in active treatment (37%) or at advanced disease (26%) and breast cancer diagnosis (28%). 85% of users presents high or severe levels of distress, manifesting as the main reason for consultation regarding emotional distress arising from the disease (42%). The number of intervention sessions conducted varies significantly according to the complaint. To conclude, indication that psychological intervention is requested on those stages of the disease where the levels of distress are clearly superior and deterioration of quality of life is significant. Therefore, it is essential to stress the importance of psychological care in cancer patients.
Keywords: Distress; cancer; screening; triage; psychosocial adjustment.